Firm Value: The Mediating Effects of Capital Structure on Profitability, Size, and Asset Structure - Mohammad Alvin Nur Rohman; Fitriyah, Fitriyah (International Journal of Science, Technology & Management, 2024)
This study aims to determine the effect of profitability, company size, and asset structure on firm value with capital structure as a mediating variable. The research method used is quantitative method using secondary data. Secondary data is obtained through the annual financial statements of healthcare sector companies that have gone public listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 period totaling 33 companies. Sampling using purposive sampling and obtained 19 companies. Based on the results of partial regression analysis and path analysis, it can be concluded that profitability has a negative effect on capital structure, company size has no effect on capital structure, asset structure affects capital structure, profitability and capital structure affect firm value, company size and asset structure have no effect on firm value, capital structure is not able to mediate the relationship between profitability, company size, and asset structure on firm value.